Effectiveness of Video-Based Cardiac Health Training on Health Behavior in Acute Coronary Syndrome Patients - Rika Suryana; Heny Suseani Pangastuti; Khudazi Aulawi (JKG (JURNAL KEPERAWATAN GLOBAL), 2026)
Background: Hospital readmissions among patients with Acute Coronary Syndrome (ACS) are frequently linked to unhealthy lifestyle behaviors such as poor diet, physical inactivity, smoking, and medication nonadherence. These modifiable risk factors significantly contribute to recurrent events and adverse outcomes, highlighting the need for effective secondary prevention strategies. Video-based health education offers a consistent and scalable approach to support behavioral change. This study aimed to evaluate the effectiveness of a video-based cardiac health education program in improving healthy behaviors among ACS patients.  Methods: A quasi-experimental, non-equivalent control group design was employed involving 57 ACS patients without severe complications. Participants were recruited via consecutive sampling and assigned to either the intervention group (n = 27) or control group (n = 30). The Modified Cardiac Health Behavior Scale (MCHBS) was used to assess healthy behaviors at baseline and after the intervention. The intervention comprised a video-based cardiac health education program with a 21-day follow-up period. Data were analyzed using paired sample t-tests for within-group comparisons and independent t-tests for between-group differences. Results: Baseline healthy behavior scores did not differ significantly between groups (p>0.05). Post-intervention, both groups showed significant improvement; however, the intervention group demonstrated a significantly greater increase (M±SD = 24.85±5.45) compared to the control group (M±SD = 10.67±6.57), with a mean difference of 14.18 (p<0.001) and a large effect size (Hedges’ g = 2.337).  Conclusion: Video-based cardiac health education effectively promotes healthier behaviors in ACS patients and holds promise as a scalable intervention to enhance secondary prevention and reduce hospital readmissions.